2018
DOI: 10.1111/1759-7714.12636
|View full text |Cite
|
Sign up to set email alerts
|

Present and changing trends in surgical modalities and neoadjuvant chemotherapy administration for female breast cancer in Beijing, China: A 10‐year (2006–2015) retrospective hospitalization summary report‐based study

Abstract: BackgroundThis study was conducted to describe present and changing trends in surgical modalities and neoadjuvant chemotherapy (NACT) in female breast cancer patients in China from 2006 to 2015.MethodsData of 44 299 female breast cancer patients from 15 tertiary hospitals in Beijing were extracted from hospitalization summary reports. Surgeries were categorized into five modalities: breast‐conserving surgery (BCS), simple mastectomy (SM), modified radical mastectomy (MRM), radical mastectomy (RM), and extensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 83 publications
1
20
0
Order By: Relevance
“…There is only sparse comparable data on the use of neoadjuvant chemotherapy in recent years. Some reports showed rising rates of NACT of 39.7% in 2014 in China 35 and 35.2% for 2009 to 2011 in South Africa 36 . The use of NACT is also rising in the US but remains at a comparative low level with 23.5% in 2012 37 or 24.0% in 2011 38 …”
Section: Discussionmentioning
confidence: 99%
“…There is only sparse comparable data on the use of neoadjuvant chemotherapy in recent years. Some reports showed rising rates of NACT of 39.7% in 2014 in China 35 and 35.2% for 2009 to 2011 in South Africa 36 . The use of NACT is also rising in the US but remains at a comparative low level with 23.5% in 2012 37 or 24.0% in 2011 38 …”
Section: Discussionmentioning
confidence: 99%
“…However, in most developing countries, such as China, the BCR is only approximately 20%, compared to 50%-80% in Western countries [6,16,17]. Even in some leading centres in China, the BCR is only 30% [18]. Because of the low BCR in developing countries and the absence of evidence for ALND omission in Eastern populations, most clinicians in developing countries such as China still hold a conservative view and recommend ALND for patients with positive SLNs [16].…”
Section: Discussionmentioning
confidence: 99%
“…At present, the main treatments of BC were surgery, radiotherapy, chemotherapy, targeted therapy and hormone therapy [44,45] . Among them, surgery can signi cantly reduce the mortality rate, which is the most critical step in the treatment of breast cancer, there are ve common surgical methods: Breast conserving surgery (BCS), simple mastectomy (SM), modi ed radical mastectomy (MRM), radical mastectomy (RM) and extensive radical mastectomy (ERM) [46] . Among them, Bartelink H et al reported that BCS has the equivalence with mastectomy [47] .…”
Section: Discussionmentioning
confidence: 99%